"Saúde pra dar e vender": a EBSERH como um aspecto do desmantelamento da saúde pública - Barbara Katherine Faris Biondini (2018)
Constitutionally, in Brazil, health has as a precept to be a right of the population and a duty of the State. However, in the 28 years that have passed since the last Federal Constitution and the promulgation of the Unified Health System (SUS), we see that the principles that govern it have not been implemented. Parallel to this context, in a decentralization movement consonant with the neoliberal prerogatives, the State's management reforms were carried out, in which the Social Organizations were created, with the objective of acting in the management of sectors that, in times of reform, were deemed not to be plus an exclusive responsibility of the state, as well as health-related activities. In line with this movement, more recently, the Brazilian Hospital Services Company (EBSERH) was created for the management of federal university hospitals. Thus, the objective of this work was to understand the progress of the dismantling of the public health service through the implementation of Ebserh in the management of university hospitals. Thus, we seek to understand questions about the insertion of the company in university hospitals, and the transformations caused, both in management and in the conditions and working relationships of workers. We build on dialectical historical materialism and share Marx's vision of his commitment to the working class and its emancipation. The theoretical framework of this project is based on reflections on health-disease and health praxis in capitalism, and the research instruments used were bibliographic surveys, interviews, observation and documentary analysis. We conclude that the Ebserh can be understood as another strategy of capital advancement in health practice, acting in the deterioration of public services in this sector